Bedtime Salivary Cortisol and Depressive Symptoms in Older Adults Living With Dementia. (17th December 2021) - McPhillips, Miranda; Petrovsky, Darina; Huang, Liming; Adriana, Adriana; Hodgson, Nancy; Dong, Fanghong
Abstract: The dysregulation of cortisol has been associated with depressive symptoms in older adults. To date, no prospective longitudinal studies have examined whether salivary cortisol is a risk factor for depressive symptoms in persons living with dementia (PLWD). With a sample of 123 PLWD, baseline salivary cortisol was collected at awaking, 30 minutes after awaking, and bedtime. Depressive symptoms were assessed at baseline and the four-week follow-up. Cortisol indicator were centered. Baseline bedtime cortisol level was significantly associated with depressive symptoms in a curvature style while controlling age, gender, and baseline depressive symptoms (𝛽=3.76 for linear term and 𝛽=-1.57 for quadratic term, both ps<0.04). No other baseline cortisol measures were significant prospective predictors. Our results suggest the bedtime cortisol was a significant risk factor for depressive symptoms in PLWD. These findings suggest that bedtime cortisol may play a role in the etiology of depressive symptoms in PLWD.